Adaptation of recently released improved orange flesh sweet potato (Ipomoea batatas L.) varieties in Southwestern Ethiopia (International Journal of Agricultural Research, Innovation and Technology, 2023)
Most sweet potato varieties currently grown by farmers are poorly adapted, have low root yields, less nutritive and white fleshed which have no beta carotene, a precursor to vitamin “A”. However, among the cheapest and richest sources of vitamin A; orange fleshed sweet potato varieties were rich in beta carotene are well accepted by young children. Hence the aim of this research project was conducted to evaluate the adaptability and performance of improved orange-fleshed sweet potato varieties on yield and other yield related traits during the 2020 main cropping season in southwest Ethiopia. The varieties used were Tulla, Kulfo, Guntutie, Vita, Kabode, Alamura and Dilla. The experiment was carried out using a randomized block design with three replications. The analysis of variance over locations depicted significant differences (p ≤0.05) among varieties for most of the studied traits. In this study, Alamura (31.42 t ha-1) and Dilla (27.8 t ha-1) varieties give a high yield among seven evaluated orange-fleshed sweet potato varieties. Based on farmer test preference, the first and second rank of test preference was recorded from Alamura and Dilla variety. Therefore, by considering both farmer’s test preference and the yield potential of the variety, Alamura and Dilla were selected as high yields and have the best test preference. Therefore, to fill the gap vitamin “A” deficiency at the community level Alamura and Dilla were selected as the best orange fleshed variety that has the best test preference with the highest yield in the humid tropics of Southwestern Ethiopia and these two varieties were recommended for production. Finally, since the result of this finding was based on data gathered from two locations and only one cropping season to test adaptability. So, one more additional season evaluation is necessary and also further studies are required to generate more reliable information on performance, nutrition and resistance to disease.Int. J. Agril. Res. Innov. Tech. 12(2): 111-116, December 2022